Sam Houston : The Life and Times of the Liberator of Texas, an Authentic American Hero - Williams, John Hoyt (New York : Promontory, 1998)
Describes the life and times of American hero, Sam Houston.
Includes bibliographical references and index.
10-A.
Keywords: Houston, Sam, -- 1793-1863; United States -- Congress -- Biography; Governors -- Biography -- Texas; Legislators -- Biography -- United States; Texas -- Biography